(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: To improve care, it is crucial to evaluate results and identify indicators that predict serious complications in children having heart surgery. This article aims to evaluate the general health of children who underwent to cardiac surgery as well as post-operative complications. Methods: A study was conducted in Baghdad, Iraq, between January 2023 and October 2024, in which 87 children who underwent cardiac surgery were recruited. The study documented the pathological outcomes of children during and after surgery, including morbidity, mortality, and complications. Furthermore, a questionnaire was administered to assess the general health-related quality of life of the children. Results: A total of 87 children who underwent cardiac surgery were included in this study. The age of the subjects ranged from 7 to 10 years, with 37.93% of the male and 45.98% of the female. Intraoperative outcomes included cardiopulmonary bypass time (92.51 ± 25.33 minutes), intensive care unit admission (34.13 ± 11.19), and ventilator use (13 cases). Death occurred in 13.79% of cases. Postoperative complications included seizure (5.75%), wound infection (3.45%), and pleural effusion (3.45%), with a total of 31.03% of cases experiencing complications. Conclusion: The present study revealed that approximately 13% of children had succumbed, while 31% of children exhibited complications. Despite this, cardiopulmonary bypass was identified as an ideal and effective procedure, with subsequent factors having a detrimental impact on children’s physical and social well-being.